Neodymium‐doped yttrium aluminium garnet (Nd:YAG) 1064‐nm picosecond laser vs. Nd:YAG 1064‐nm nanosecond laser in tattoo removal: a randomized controlled single‐blind clinical trial. (29th January 2017) - Pinto, F.; Große‐Büning, S.; Karsai, S.; Weiß, C.; Bäumler, W.; Hammes, S.; Felcht, M.; Raulin, C.
Summary: Background: For decades, nanosecond lasers (NSLs) have been used to remove tattoos. Since 2012, pulses of picosecond lasers (PSLs) have been available for tattoo removal. Based on a few observational studies, the claim has been made that PSLs are considerably more effective while showing fewer side‐effects in comparison with NSLs. Objectives: To compare the efficacy and side‐effects of a PSL side by side with an NSL for tattoo removal. Methods: Twenty‐one patients with 30 black tattoos were treated with PSL and NSL in a split‐study design in two sessions at intervals of 6 weeks. The safety and efficacy of laser treatments were determined by blinded observers assessing randomized digital photographs in this prospective clinical study. The primary end point was the clearance of the tattoos ranging in quartiles from 0% to 100%; secondary end points were side‐effects and pain. Results: The average clearance overall as evaluated showed no statistical difference between NSL and PSL ( P = 1·00). Using a visual analogue scale (0 = no pain, 10 = maximum pain), a value of 3·8 ± 1·0 was reported for the PSL, which was statistically different from NSL (7·9 ± 1·1, P < 0·001). Transient side‐effects were observed, as well as hypo‐ and hyperpigmentation, but there was no statistically significant difference between PSL and NSL. Conclusions: After two treatments of black tattoos with a neodymium‐doped yttrium aluminium garnet laser (1064 nm), the use of picosecond pulses does not provide better clearance than nanosecond pulses. However, pain is less severe when using a PSL. Abstract : What's already known about this topic? Laser tattoo removal is increasing in proportion to the steadily growing incidence of tattoos. The industry and a few publications postulate that picosecond lasers are more efficacious in clearing tattoos and have fewer side‐effects than nanosecond lasers. What does this study add? This is the first randomized controlled trial to compare and analyse the clearance of tattoos. This study evaluates the side‐effects of two commercially available nano‐ and picosecond lasers in a split‐study design. Picosecond pulses do not provide better clearance than nanosecond pulses, but do result in less pain. Linked Comment: Ross. Br J Dermatol 2017; 176 :299–300 .